COVID-19 CONFINEMENT CHANGED DIETARY BEHAVIOUR IN INDONESIA - Nafisah Eka Puteri; Ayu Diah Damayanti; Maryam Jameelah; Sarah Giovani (Universitas Pahlawan, 2022)
Pandemic has affected various sectors and caused alteration in many fields. Dietary behaviour might change due to COVID-19 pandemic. Previous studies related to dietary behaviour during COVID-19 pandemic had been done in several countries. However, there is limited study on consumption pattern in Indonesia during pandemic. Our work focused on observing the changes in dietary behaviour of Indonesian during COVID-19 confinement. In order to reach the purpose, a cross-sectional study was conducted by using online questionnaire distributed using social media. The information of respondents related to socio-demographic and situation during confinement were gathered. Furthermore, respondents were also inquired about the consumption of vegetable, fruit, supplement and vitamin, soft drink, snack, and jamu or empon-empon during COVID-19 confinement. The results will be useful for industries and government due to the lack of information related to dietary behaviour during COVID-19 confinement in Indonesia. The results found an increasing and decreasing consumption of certain food group due to economic situation, stress and anxiety, and also food accessibility. COVID-19 confinement also changed the way in preparing meal. This condition was also affected by the increasing of respondents’ awareness on healthier lifestyle. A longer observation accompanied by Body Mass Index information is able to illustrate the impact of dietary behaviour during COVID-19 pandemic on chronic disease tendency.